Financial Technology (FinTech) dan Prospeknya dalam Industri Keuangan Syariah di Indonesia - Ahmad Shodiq; Ahmad Rifa’i; Syiva Ratna Sari; Ingka Diviana Awalina (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Financial technology/Fintech is the result of a combination of financial services and technology which ultimately changed the business model from conventional to moderate, where initially you had to pay face to face and bring a certain amount of cash, now you can make long distance transactions by making payments that can be made in a matter of seconds. just seconds. The use of applications in business activities is used to maximize time and costs to produce desired profits. With this need, currently many application developers are offering their products to support business activities. Buying and selling activities, borrowing funds, even sending money via online applications makes everything easier so that people are no longer limited by distance and time. The research objective is to determine the level of understanding of the use of Fintech. The type of research used in this research is literature study obtained from various sources.